AT collective in Belgium - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Established by several Belgium NGOs involved in development work, the Collective for the Exchange of Appropriate Technology (COTA) tries to promote simple technologiesthat require little capital investment and make use of local skills and...